2018
DOI: 10.1186/s40657-018-0138-1
|View full text |Cite
|
Sign up to set email alerts
|

Variability among autumn migration patterns of Mongolian Common Shelducks (Tadorna tadorna)

Abstract: Background: Avian migrants moving between common breeding and wintering areas may adopt different migration routes, and consequently affect timing. However, this pattern has rarely been investigated, especially in waterbirds. Moreover, autumn migration patterns of the Common Shelduck (Tadorna tadorna) have never been studied. Methods:We used GPS transmitters to track, for the first time, the autumn migration of the Common Shelduck in East Asia (n = 14). Results:The Common Shelduck undertook a broadly northwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In this study, we only used locations categorized as A, B, and C. The migration routes and heat maps were created, and the cumulative migration distance was calculated via the geometry function in ArcGIS 10.2. The start and end of the migration time were defined as the date from which the individuals departed from and arrived at the breeding/summering or wintering sites (Wang et al, 2018). Migration duration was calculated as the time between the individual's start and end of the migration.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we only used locations categorized as A, B, and C. The migration routes and heat maps were created, and the cumulative migration distance was calculated via the geometry function in ArcGIS 10.2. The start and end of the migration time were defined as the date from which the individuals departed from and arrived at the breeding/summering or wintering sites (Wang et al, 2018). Migration duration was calculated as the time between the individual's start and end of the migration.…”
Section: Discussionmentioning
confidence: 99%
“…Their species, body mass, and sex were recorded. A 17 g solar-powered GPS-GSM backpack transmitter (model HQBG2715S, Hunan Global Messenger Technology Co., Ltd., Hunan, China) was attached to each duck which fitted the criterion that mounted satellite transmitters should weigh ≤ 3% of the bird's body weight (Wang et al 2018; Kuang et al 2022). The individuals equipped with backpacks were placed into cages for further observation for about 1 hour before releasing.…”
Section: Methodsmentioning
confidence: 99%
“…The development of satellite tracking technology has made it possible to conduct long-term studies providing accurate and detailed spatial data on the migration of large waterbirds, such as White-naped Cranes ( Grus vipio ), Black-necked Cranes ( Grus nigricollis ), and Whooper Swans ( Cygnus cygnus ; Higuchi et al 1996; Wang et al 2020; Wang et al 2020; Ao et al 2020). In addition, the development of lighter satellite transmitters has recently allowed this technique to be used to study wild ducks (Takekawa et al 2010; Wang et al 2018). Eastern Spot-billed Ducks ( Anas zonorhyncha ) and Mallards ( Anas platyrhynchos ) are two of the dominant wintering waterfowl species in Shanghai City (Pei et al 2007), and have been reported to breed in Northeast Asia (Zhao 2001).…”
mentioning
confidence: 99%
“…For each individual, we defined spring migration as starting from the last position received from the overwintering area (Yangtze River floodplain) and terminating with the first position of a series of positions received from the summering grounds (Mongolian Plateau); autumn migration, summering, and wintering periods followed similar definitions (Li et al 2020a). We applied the methods of Wang et al (2018) to segment movement tracks, identifying flight legs between successive stopover sites, which were defined as locations where a bird did not move >30 km in a 48-h period (Kölzsch et al 2016, Li et al 2020a). Using this approach, we obtained the stages during the summering/wintering period and spring/autumn migration of each track of each individual to describe the habitats that these birds used for feeding and resting.…”
Section: Methodsmentioning
confidence: 99%